A Topical Treatment Optimization Programme (TTOP) improves clinical outcome for calcipotriol/betamethasone gel in psoriasis: results of a 64‐week multinational randomized phase IV study in 1790 patients (PSO‐TOP). (1st July 2017) - Reich, K.; Zschocke, I.; Bachelez, H.; de Jong, E.M.G.J.; Gisondi, P.; Puig, L.; Warren, R.B.; Ortland, C.; Mrowietz, U.
Summary: Background: Around two‐thirds of patients with psoriasis do not adhere to topical treatment. The Topical Treatment Optimization Programme (TTOP), a five‐element tool, includes guidance for the conversation between dermatologists/nurses and patients, patient information material, telephone/e‐mail helpdesks and treatment reminders. It has been developed by patients and dermatologists to help increase adherence to treatment in psoriasis. Objectives: To compare TTOP with standard of care ('non‐TTOP') within a large European investigator‐initiated study, PSO‐TOP (clinicaltrials.gov NCT01587755). Methods: Patients with mild‐to‐moderate psoriasis received calcipotriol/betamethasone dipropionate gel as standardized study medication and were randomized 1 : 1 to either TTOP or non‐TTOP management. Study medication was applied once daily for 8 weeks followed by 'as needed' application for an additional 56 weeks. Response was defined as a Physician's Global Assessment (PGA) of 'clear' or 'almost clear'. Results: In 1790 patients (full analysis set), response rates after 8 weeks (primary objective) were significantly higher for TTOP (36·3%) than for non‐TTOP (31·3%, P = 0·0267). Better clinical outcome was accompanied by higher rates of patients feeling well informed about their skin condition, treatment and other factors related to adherence, but the Dermatology Life Quality Index was not statistically different. TTOP patients regarded the structured one‐to‐one conversations with their dermatologist/nurse as the most important element of TTOP. Conclusions: Patients randomized to the TTOP intervention had a better clinical response than patients receiving standard of care. Improved communication between the healthcare provider and patient might be an important element in increasing adherence to topical therapy in psoriasis.